Kulkul in Global Era of Communication Advancement - Ida Bagus Brata; Ida Bagus Nyoman Mantra (Soshum: Jurnal Sosial dan Humaniora, 2018)
Communication is a form of interaction between the communicator and the communicant, requiring certain media in order for the message to be conveyed well. Kulkul as a communication medium has a significant role and several functions as a means to unite the community. For the people of Bali, kulkul has a high spirit of togetherness. Every time the sound of kulkul is heard, the residents will be present at the place previously agreed upon. With the power of its sound, kulkul is able to create unwritten rules. It is obeyed by all members of the community. It does not matter whether they are officials, farmers, caste people or ordinary people, all of them have to gather when they hear kulkul. This is because the sound of kulkul is a significant order that must be obeyed by the members of the community. The development and advancement of information and communication technologies in various forms of digital media, which make all activities more effective and efficient cause kulkul function as a traditional communication medium in an intense pressure from electronic media. Kulkul as traditional communication medium for the Balinese is deemed to be able to bridge the communication among the Balinese